Tìm x để P<\(1-\sqrt{x}\)
P=\(\frac{2\sqrt{x}-1}{\sqrt{x}+1}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(P=\left(\frac{1}{x-\sqrt{x}}-\frac{1}{\sqrt{x}-1}\right).\frac{x-2\sqrt{x}+1}{\sqrt{x}-1}\)
\(=\left(\frac{1}{\sqrt{x}\left(\sqrt{x}-1\right)}-\frac{1}{\sqrt{x}-1}\right).\frac{\left(\sqrt{x}-1\right)^2}{\sqrt{x}-1}\)
\(=\left(\frac{1}{\sqrt{x}\left(\sqrt{x}-1\right)}-\frac{1}{\sqrt{x}-1}\right).\left(\sqrt{x}-1\right)\)
\(=\frac{1}{\sqrt{x}-1}\)
Để \(P< \sqrt{P}\)
\(\Rightarrow\hept{\begin{cases}P\ge0\\P^2< P\end{cases}}\)
\(\Rightarrow\hept{\begin{cases}P\ge0\\P^2-P< 0\end{cases}}\)
\(\Rightarrow\hept{\begin{cases}P\ge0\\P\left(P-1\right)< 0\end{cases}}\)
\(\Rightarrow\hept{\begin{cases}P\ge0\\0< P< 1\end{cases}}\)
\(\Rightarrow0< P< 1\)
+ ) \(P>0\Rightarrow\frac{1}{\sqrt{x}}-1>0\Rightarrow\frac{1}{\sqrt{x}}>1\)
\(\Rightarrow\sqrt{x}< 1\Rightarrow0< x< 1\)
+ \(P< 1\Rightarrow\frac{1}{\sqrt{x}-1}< 1\Rightarrow\frac{1}{\sqrt{x}}< 2\)
\(\Rightarrow\sqrt{x}>\frac{1}{2}\Rightarrow x>\frac{1}{4}\)
\(\Rightarrow\frac{1}{4}< x< 1\)
a ) \(ĐKXĐ\hept{\begin{cases}x\ge0\\x\ne4\\x\ne9\end{cases}}\)
\(A=\frac{2\sqrt{x}-9}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}-\frac{\left(\sqrt{x}+3\right)\left(\sqrt{x}-3\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}+\frac{\left(2+\sqrt{x}+1\right)\left(\sqrt{x}-2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}\)
\(=\frac{2\sqrt{x}-9-x+9+2x-4\sqrt{x}+\sqrt{x}-2}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}\)
\(=\frac{x-\sqrt{x}-2}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}\)
\(=\frac{\left(\sqrt{x}-2\right)\left(\sqrt{x}+1\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x-3}\right)}\)
\(=\frac{\left(\sqrt{x}-2\right)\left(\sqrt{x}+1\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}=\frac{\sqrt{x}+1}{\sqrt{x}-3}\)
b ) \(A=\frac{\sqrt{x}+1}{\sqrt{x}-3}< 1\)
\(\Leftrightarrow\frac{\sqrt{x}+1}{\sqrt{x}-3}-1< 0\)
\(\Leftrightarrow\frac{\sqrt{x}+1-\sqrt{x}+3}{\sqrt{x}-3}< 0\)
\(\Leftrightarrow\frac{4}{\sqrt{x}-3}< 0\)
\(\sqrt{x}-3< 0\)
\(\Leftrightarrow x< 9\)
Vậy với \(0\le x\le9;x\ne4\) thì ...
Chúc bạn học tốt !!!